Content area reading : integration with the language arts - Jacobson, Jeanne M. (Albany, N.Y. : Delmar, 1998)
Characteristics of content area learning and teaching. Before, during, and after: strategies for content area learning and teaching. Building strengths, meeting needs, and making connections. Extending content area learning.
Keywords: Language teaching; Language arts; Correlation; Teaching; Language arts -- Correlation with content subjects